The impact of undergraduate students’ mathematics anxiety and self-concept on their self-regulated learning and academic achievement - Dian Cahyawati; Nita Delima; Muji Gunarto (Jurnal Elemen, 2023)
Several types of research showed math anxiety as the learning outcome, but another showed that as the predictor variable. Math anxiety was predicted based on other variables, such as self-regulated learning and self-concept. Self-regulated learning is associated with academic achievement. This study aimed to obtain valid and significant indicators of each latent variable and to develop the structural model of those latent variables on students’ academic achievement. The research used an interval scale questionnaire to measure all latent variables except academic achievement. The PLS-SEM was applied by SmartPLS software. The structural model showed that math anxiety directly affected academic achievement but indirectly affected self-regulated learning, which is self-concept as the mediating variable. For students with low math anxiety, their self-regulated learning tends to be high by controlling their self-concept in math.